2015
DOI: 10.1021/op500297g
|View full text |Cite
|
Sign up to set email alerts
|

Quality by Design in Action 2: Controlling Critical Material Attributes during the Synthesis of an Active Pharmaceutical Ingredient

Abstract: Quality by Design (QbD) is of paramount importance not only for patient safety but also for the timely and uninterrupted supply of products at affordable prices into the market. Both of these objectives can be achieved only through a robust process, and one of the major obstacles for developing a robust process is the quality of input materials and reagents used for the manufacture of active pharmaceutical ingredients (APIs). This article demonstrates the use of QbD methodology to optimize the quality of input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The adaption of QbD principles to continuous manufacturing for the understanding of the impact of process parameters and material attributes to product quality will be important. 159,160 Most continuous manufacturing platforms allow for the adoption of increased levels of controls, such as set points and alarms, in-process monitoring, process control and material diversion. The control strategy should incorporate these additional functionalities and be able to assure process performance and product quality.…”
Section: Risk Assessments For Continuousmentioning
confidence: 99%
“…The adaption of QbD principles to continuous manufacturing for the understanding of the impact of process parameters and material attributes to product quality will be important. 159,160 Most continuous manufacturing platforms allow for the adoption of increased levels of controls, such as set points and alarms, in-process monitoring, process control and material diversion. The control strategy should incorporate these additional functionalities and be able to assure process performance and product quality.…”
Section: Risk Assessments For Continuousmentioning
confidence: 99%
“…In order to maintain a high publication standard, some minimum should be achieved in terms of process duration and volumetric reactor turnovers. Since residence times encountered in CM can range widely from seconds to hours, it is difficult to suggest a discrete number of reactor turnovers, but it should be demonstrated that a state of control (or “steady state”) was achieved, wherein product quality is acceptable over the duration of the continuous run . For most residence times, a range of acceptable total processing times for a single, uninterrupted run could be 2–48 h to demonstrate the robustness of the process as well as supporting equipment such as pumps, process analytical technology (PAT), and the pressure regulation system.…”
Section: Suggested Guidance For Authors Of CM Submissions To Opranddmentioning
confidence: 99%
“…Introducing the concept of Quality by Design in regulations relating to medicinal product manufacturing has improved the understanding of production processes. Improving product quality is a priority, and there has been an increase in the number of reports related to optimization of API manufacturing processes through DoE. , The range of applications of DoE is broad and extends to a variety of chemical reactions and the development of a wide range of crystallization and analytical methods . In this work, we investigated the optimization of an orantinib API crystallization process with DoE to control the amount of residual solvent and the particle size distribution.…”
Section: Introductionmentioning
confidence: 99%